Workplace incivility and burnout among Indonesian Migrant workers in South Korea - Muchammad Ferry Khusnul Ma'ab Maaya'ba; Ika Rahma Susilawati (Universitas Ahmad Dahlan, 2025)
Workplace incivility has emerged as a significant psychosocial hazard in various occupational settings. Migrant workers are particularly vulnerable due to linguistic, cultural, and structural challenges. This study examines the relationship between workplace incivility and burnout among Indonesian migrant workers in South Korea. Data were collected from 276 respondents through purposive and snowball sampling, using a quantitative survey design. The Indonesian adaptation of the Workplace Incivility Scale and the Maslach–Trisni Burnout Inventory were employed to measure incivility and burnout. Descriptive analysis indicated that a substantial proportion of participants reported moderate to high levels of both variables. Simple linear regression analysis revealed that workplace incivility significantly and positively predicted burnout levels, accounting for a substantial proportion of the variance (R²=0.879). Pearson correlation analysis further showed that instigated incivility had the strongest association with emotional exhaustion, while supervisor and coworker incivility were significantly correlated with all burnout dimensions. An independent t-test revealed that respondents with children reported higher burnout levels, whereas marital status, age, and prior overseas experience were not significant predictors of burnout. These results demonstrate that interpersonal mistreatment meaningfully contributes to the psychological strain among Indonesian migrant workers. The findings extend empirical evidence on the incivility–burnout link to a new cultural context and highlight the need for transnational labor policies, particularly through collaboration between the Kementerian Pelindungan Pekerja Migran Indonesia (KP2MI) and the Human Resources Development Service of Korea (HRD Korea) to incorporate psychosocial protection, respectful communication, and mental health support into the Employment Permit System (EPS).